Distribution patterns of HLA-A*, B*, DRB1* allele groups among persons who underwent COVID-19 - L. N. Bubnova; I. E. Pavlova; A. S. Berkos; M. A. Terentyeva; T. V. Glazanova; L. V. Erokhina; E. V. Belyaeva; A. V. Chechetkin; N. S. Bashketova; I. G. Chkhindzheria; M. А. Kozhemyakina; D. V. Azarov; et al. (Медицинская иммунология, 2021)
The main histocompatibility complex — HLA system (Human Leukocyte Antigens) is among the most important genetic factors determining response of humans to infectious agents. The key role that HLA molecules play in immune response is to present the pathogen-derived peptides. Enormous molecular variability of HLA alleles in human populations have attracted close attention and became the basis for numerous studies aimed at evaluating the role of HLA genotypes for individual features of immune response to COVID-19, the new infection caused by SARS-CoV-2 β-coronavirus. Many studies have focused on search of specific alleles associated with both susceptibility and resistance to this disease. Separate HLA patterns were reported already. These patterns may be either universal to several populations, or rather peculiar, since distribution of HLA genes is different for various populations, depending on the living conditions, including specific protection from environmental pathogens. Therefore, it is evident that individual effects of HLA genotype upon occurrence and course of SARS-CoV-2 infection should be performed in comparison with the HLA distribution among the residents of appropriate region. The objective of this study was to compare the distribution of HLA-A*, B*, DRB1* allele groups, and to analyze the frequencies of HLA-AB-DRB1 haplotypes in subjects with COVID-19 (n = 138), compared with the control group presented by residents of the North-Western Russia (n = 1456). The most significant differences between COVID-19 patients compared with a group from control population were revealed for the groups of HLA-A* alleles: the frequencies of HLA-A*02 and HLA-A*26 were significantly reduced (39.86% versus 51.72%, χ2 = 7,58, and 4.35% versus 9.07%, χ2 = 4.17, respectively). At the same time, the frequency of HLA-A*29 was increased more than 2-fold (5.80% versus 2.47%, χ2 = 4.03). This finding suggests that the allele groups A*02 and A*26 are associated with reduced likelihood of the disease, while A*29, is an apparent factor predisposing for susceptibility to the disease. It was found that occurrence of definite HLA haplotypes, including the A*02 allele group, is less common in persons who have undergone COVID-19, and are ranged at the 4th, 7th and 10th positions in frequency, while in the population control group such HLA haplotypes took the 3rd, 4th, 7th and 8th places. Further evaluation of the HLA gene polymorphism will allow to understand the predetermined immunogenetic basis for susceptibility, as well as clinical severity of COVID-19.